Longitudinal Analysis of Biologic Correlates of COVID-19 Resolution: Case Report - Bruiners, Natalie; Guerrini, Valentina; Ukey, Rahul; Dikdan, Ryan J.; Yang, Jason H.; Mishra, Pankaj Kumar; Onyuka, Alberta; Handler, Deborah; Vieth, Joshua; Carayannopoulos, Mary; Guo, Shuang; Pollen, Maressa; et al. (Frontiers in Medicine, 2022)
While the biomarkers of COVID-19 severity have been thoroughly investigated, the key biological dynamics associated with COVID-19 resolution are still insufficiently understood. We report a case of full resolution of severe COVID-19 due to convalescent plasma transfusion. Following transfusion, the patient showed fever remission, improved respiratory status, and rapidly decreased viral burden in respiratory fluids and SARS-CoV-2 RNAemia. Longitudinal unbiased proteomic analysis of plasma and single-cell transcriptomics of peripheral blood cells conducted prior to and at multiple times after convalescent plasma transfusion identified the key biological processes associated with the transition from severe disease to disease-free state. These included (i) temporally ordered upward and downward changes in plasma proteins reestablishing homeostasis and (ii) post-transfusion disappearance of a subset of monocytes characterized by hyperactivated Interferon responses and decreased TNF-α signaling. Monitoring specific dysfunctional myeloid cell subsets in peripheral blood may provide prognostic keys in COVID-19.